The Correlation between Brain Dominance and Language Learning Strategy Use of English Preparatory School Students - Özyel, Meryem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The vitality of learning strategies is clearly evident since there are many studies and books published in this area. This study aims at investigating the correlation between brain dominance and language learning strategies used by the non-native English speakers learning English in English Preparatory School at Cyprus International University. The sample of the study consisted of 187 English preparatory school students. The participants’ hemispheric dominance was determined by the “Brain Dominance Inventory” (BDI) which was re-arranged by Davis (1994) and was translated into Turkish by Kök (2005). To identify the strategic preferences of the participants, “Strategy inventory for language learning” (SILL) was used. This inventory was designed by Oxford (1990) to identify the strategies that EFL learners use to improve their language learning. The inventory was translated into Turkish by Cesur and Fer (2007). Bonferroni test was used in order to investigate differences among all possible pairs of means. The study concluded that left-brained participants use social and metacognitive strategies more than right and whole-brained participants. However, no other significant differences were found between any of the pairs in the study. It is inevitable that learners with different brain dominances are present in language classrooms. In this respect, identifying learners’ brain dominance is crucial since it is believed to be influential on the preference of strategy use. For effective language learning, strategies could be taught to language learners, and if it is done in accordance with brain dominance type, it is expected to be more efficient way of teaching strategies. Keywords: Brain dominance, language learning strategies, EFL students.

ÖZ : Öğrenme stratejierinin önemi bu alanda birçok çalışma ve kitap yayımlanmış olmasından da açıkça ortadadır. Bu çalışma Uluslararası Kıbrıs Üniversitesi’nde okuyan ve anadili İngilizce olmayan İngilizce hazırlık okulu öğrencilerinin kullandığı dil öğrenme stratejileri ve beyin basklınlığı arasındaki ilişkiyi incelemeyi amaçlamaktadır. Araştırmanın örneklemi 187 hazırlık okulu öğrencisinden oluşmaktadır. Katılımcıların beyin baskınlığı Davis (1994) tarafından düzenlenmiş ve Kök (2005) tarafından Türkçe'ye tercüme edilmiş Beyin Baskınlığı Envanteri ile belirlenmiştir. Katılımcıların strateji kullanım tercihlerini belirlemek için de "Dil Öğrenme Stratejileri Envanteri" kullanılmıştır. Bu envanter Oxford (1990) tarafından öğrencilerin yabancı dil öğrenimlerini geliştirmek için kullandıkları stratejileri belirlemek için tasarlanmıştır. Envanter Cesur ve Fer (2007) tarafından Türkçe'ye tercüme edilmiştir. Araştırmada değişkenler arasındaki farklılıkları incelemek için Bonferroni test kullanıldı. Araştırmada sol beyin baskınlığı olan katılımcıların sağ ve tüm beyin baskınlığı olan katılımcılardan daha fazla üstbilişsel ve sosyal stratejiler kullandığı sonucuna varılmıştır. Ancak, diğer çiftler arasında istatiksel açıdan başka anlamlı bir fark görülmemiştir. Farklı beyin baskınlığı olan öğrencilerin aynı dil sınıfında mevcut olmaları kaçınılmazdır. Bu bağlamda, öğrencilerin beyin baskınlığını belirlemek, beyin baskınlığının öğrencilerin öğrenme stratejilerini kullanım tercihleri üzerinde etkisi olması açısından önemlidir. Etkili dil öğrenimi için dil öğrencilerine stratejiler öğretilebilir, ve bu beyin baskınlık tipine uygun olarak yapıldığı takdirde strateji öğretiminin daha etkili olması beklenmektedir. Anahtar Kelimeler: Beyin baskınlığı, Dil öğrenme stratejileri, İngilizceyi yabancı dil olarak öğrenen öğrenciler.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; Brain dominance; language learning strategies; EFL students